2016
DOI: 10.1175/jcli-d-15-0710.1
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal and Interannual Variations of the Energy Flux Equator and ITCZ. Part II: Zonally Varying Shifts of the ITCZ

Abstract: The ITCZ lies at the ascending branch of the tropical meridional overturning circulation, where nearsurface meridional mass fluxes vanish. Near the ITCZ, column-integrated energy fluxes vanish, forming an atmospheric energy flux equator (EFE). This paper extends existing approximations relating the ITCZ position and EFE to the atmospheric energy budget by allowing for zonal variations. The resulting relations are tested using reanalysis data for 1979-2014. The zonally varying EFE is found as the latitude where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
102
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 34 publications
3
102
0
Order By: Relevance
“…An energetic theory has been developed over the past two decades to diagnose how processes in Earth's climate-including radiation asymmetries between hemispheres, atmosphere-ocean coupling, and energy input to the tropical atmosphere-control the zonal-mean ITCZ location [10][11][12][13][14][15][16][17][18][19][20][21]. This theory has recently been extended to understand variations of the ITCZ location with longitude [22,23]. Four recent review articles have comprehensively synthesized this body of research on the ITCZ location [1,[24][25][26].…”
Section: Earth's Deep-tropical Climate Is Dominated By the Intertropimentioning
confidence: 99%
“…An energetic theory has been developed over the past two decades to diagnose how processes in Earth's climate-including radiation asymmetries between hemispheres, atmosphere-ocean coupling, and energy input to the tropical atmosphere-control the zonal-mean ITCZ location [10][11][12][13][14][15][16][17][18][19][20][21]. This theory has recently been extended to understand variations of the ITCZ location with longitude [22,23]. Four recent review articles have comprehensively synthesized this body of research on the ITCZ location [1,[24][25][26].…”
Section: Earth's Deep-tropical Climate Is Dominated By the Intertropimentioning
confidence: 99%
“…Variants of the bifurcated ITCZ pattern exist in the present tropical climate on time scales of days or longer: daily states of the ITCZ in the eastern Pacific vary between single and double ITCZs that straddle the equator (Haffke et al, ), with increased occurrence of double‐ITCZ states during boreal spring and during La Niña episodes (Adam et al, ; Bischoff & Schneider, ; Gu et al, ; Zhang, ); infrequent seasonal occurrences of double‐ITCZ states are observed over the Indian Ocean and central Pacific (e.g., Zhang, ); a regional bifurcation from a single ITCZ in the Indian Ocean to a south Pacific convergence zone (SPCZ) and a Pacific ITCZ north of the equator is observed year round (e.g., Adam et al, ). Additionally, modern climate models tend to have more pronounced double ITCZs in the Pacific than is observed (e.g., Lin, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regions hosting a single ITCZ are characterized by monsoonal circulations, which are Hadley‐like in the zonal mean (e.g., Dima & Wallace, ). On the other hand, regions hosting double ITCZs that straddle the equator are associated with non‐Hadley‐like meridional overturning circulations: the double ITCZs lie along the rising branches of narrow meridional overturning circulations on either side of the equator, with a shared equatorial descending branch (Adam et al, ; Bischoff & Schneider, ). The bifurcation from single to double ITCZs is therefore linked to a bifurcation of the tropical overturning circulation (Bischoff & Schneider, ).…”
Section: Introductionmentioning
confidence: 99%
“…On a regional scale, Stanfield et al () used several metrics to characterize the North Pacific ITCZ, such as its width, its centerline position, and its magnitude. A number of studies have evaluated the influence of different drivers on the position of the ITCZ (e.g., Adam et al, , ; Bischoff & Schneider, , ; Harrop & Hartmann, ; Kang et al, ; Möbis & Stevens, ; Philander et al, ; Popp & Silvers, ; Vellinga & Wood, ) and the width of the ITCZ (Byrne & Schneider, ); however, the absence of a suitable terminology for describing the tropical zonal‐mean precipitation has led to a lack of clarity.…”
Section: Introductionmentioning
confidence: 99%